Implementation Research on the Effects and Results of a National Health Promotion Project - Dalbom Linda; Tuominen Miia; Löyttyniemi Eliisa; Rautava Päivi (Taylor & Francis, 2025)
The purpose of this study was to describe the implementation of the Finnish government’s 2017-2018 key project titled “Effective lifestyle counselling for social and health care cross-functionally” (VESOTE) in primary health care organizations in Southwest Finland. The study also aimed to illustrate the project’s impacts on nursing practices in primary health care organizations in terms of lifestyle counselling. Data were collected from all of the primary health care organizations in Southwest Finland by using a questionnaire. The data were analyzed qualitatively and by using descriptive statistics. The participants considered the VESOTE project important in terms of its contents. However, only individual measures of the project were adopted into practice. Organizations require tools to monitor the implementation of a new operating model. This should be taken into account when launching national projects.